Unraveling the Extracellular Metabolism of Immortalized Hippocampal Neurons Under Normal Growth Conditions - Campanella, Beatrice; Colombaioni, Laura; Nieri, Riccardo; Benedetti, Edoardo; Onor, Massimo; Bramanti, Emilia (Frontiers in Chemistry, 2021)
Metabolomic profiling of cell lines has shown many potential applications and advantages compared to animal models and human subjects, and an accurate cellular metabolites analysis is critical to understanding both the intracellular and extracellular environments in cell culture. This study provides a fast protocol to investigate in vitro metabolites of immortalized hippocampal neurons HN9.10e with minimal perturbation of the cell system using a targeted approach. HN9.10e neurons represent a reliable model of one of the most vulnerable regions of central nervous system. Here the assessment of their extracellular metabolic profile was performed by studying the cell culture medium before and after cell growth under standard conditions. The targeted analysis was performed by a direct, easy, high-throughput reversed phase liquid chromatography with diode array detector (RP-HPLC-DAD) method and by head space - solid phase microextraction-gas chromatography -mass spectrometry (HS-SPME-GCMS) for the study of volatile organic compounds (VOCs). The analysis of N=6 different batches of cells has allowed to investigate the metabolic reproducibility of neuronal cells and to describe the metabolic “starting” conditions that is mandatory for a well-grounded interpretation of the results of any following cellular treatment. An accurate study of the metabolic profile of HN9.10e cell line has never been performed before and it could represent a quality parameter before any other targeting assay or further exploration.